RESOLUSI KONFLIK DALAM PENDIRIAN RUMAH IBADAH GEREKA BETHEL INDONESIA DI KELURAHAN KEBONLEGA KECAMATAN BOJONGLOA KIDUL KOTA BANDUNG - Azka Fatina Bakti (Universitas Jenderal Ahmad Yani, 2018)
In West Java, there have been many religious conflicts with the background of the construction of houses of worship. The construction of places of worship, especially churches, often triggers conflicts with the communities around the location where the houses of worship are built. This conflict occurred mainly because the church was established in the middle of a predominantly Muslim settlement. By identifying the problem. How is the conflict resolution process in the establishment of the Indonesian Bethel Church in Kebonlega Village? This study using descriptive research methods with a qualitative approach. The result of this research is that the conflict resolution in the establishment of Indonesian Bethel Church Houses of Worship in Kebonlega Subdistrict, Bojongloa Kidul District, Bandung City is optimal. The perception is that conflicts that have been handled through surveillance in conflict areas routinely coordinate with each other to maintain a conducive situation, through deliberations and negotiations to produce solutions. with the result that the community agreed with the establishment of houses of worship and the Church Committee assisted in the form of CSR for the community, thus cooperation had been established in the community and it was hoped that it could remain in a state of long-term peace.